Analisis Risiko Operasional pada Proses Inbound Material Menggunakan Risk Matrix di PT XYZ - Ikhbal Sifaunnas; Muhammad Mansur Yafi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Inbound material delays can disrupt logistics operations, warehouse activities, and overall supply chain performance. This study aims to identify risks in the inbound material process, analyze the probability and severity of each risk, and evaluate the risk level using the Risk Matrix method to determine risk mitigation priorities at PT XYZ. This research employed a quantitative descriptive approach using historical inbound material delay data from January to December 2025, collected through observation, interviews, and company documentation. The results identified four major risks, namely vessel delays, limited vehicle availability, delays in the release of the Delivery Order (DO) by the freight forwarding company (EMKL), and traffic congestion and vehicle breakdowns. The Risk Matrix evaluation indicated that vessel delays, as well as traffic congestion and vehicle breakdowns, represent the highest-priority risks requiring immediate mitigation. The findings are expected to provide a basis for developing effective risk mitigation strategies to improve logistics operational performance and minimize inbound material delays.